Surveillance of COVID-19 vaccine effectiveness: a real-time case–control study in southern Sweden. (2nd March 2022) - Björk, Jonas; Bonander, Carl; Moghaddassi, Mahnaz; Rasmussen, Magnus; Malmqvist, Ulf; Kahn, Fredrik; Inghammar, Malin
Abstract: The extensive register infrastructure available for coronavirus disease 2019 surveillance in Scania county, Sweden, makes it possible to classify individual cases with respect to hospitalisation and disease severity, stratify on time since last dose and demographic factors, account for prior infection and extract data for population controls automatically. In the present study, we developed a case–control sampling design to surveil vaccine effectiveness (VE) in this ethnically and socioeconomically diverse population with more than 1.3 million inhabitants. The first surveillance results show that estimated VE against hospitalisation and severe disease 0–3 months after the last dose remained stable during the study period, but waned markedly 6 months after the last dose in persons aged 65 years or over.